FATE OF PARTIALLY PURIFIED C(14)-LABELED TOXIN OF CLOSTRIDIUM PERFRINGENS - Ellner, Paul D. (1961)
Ellner, Paul D. (University of Florida, Gainesville). Fate of partially purified C(14)-labeled toxin of Clostridium perfringens. J. Bacteriol. 82:275–283. 1961.—A study was made of the fate of Clostridium perfringens toxin in susceptible animals. Labeled toxin was prepared by growing C. perfringens type A in a complex casein hydrolyzate medium containing a tryptic hydrolyzate of C(14)-labeled algal protein. The toxin was purified about 30-fold (in terms of lecithinase activity) by ammonium sulfate and acetone precipitations. The tagged toxin was injected intravenously into mice and rabbits, and the disappearance from the blood stream, deposition in organs and appearance in urine and expired air determined by measurement of radioactivity. Experimental data showed that toxin disappears rapidly from the bloodstream following intravenous injection, with radioactivity appearing in the urine and expired air shortly thereafter (10 to 20 min). The organs primarily responsible for the uptake of toxin from the blood are the liver (72%), lungs (15%), kidney (8%), and spleen (5%). The toxin is not bound to skeletal muscle. Fractionation of the liver into subcellular particles by centrifugation showed the radioactivity to be concentrated in the mitochondrial fraction. These experiments indicate that the toxin is rapidly removed from the circulating blood, is metabolized, and breakdown products excreted in the urine, with 1 carbon fragments eliminated as CO(2) in the expired air.